Biocide Activity of Green Quercetin-Mediated Synthesized Silver Nanoparticles - Tasca-Gottardo, F; Tasca-Gottardo, F (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
The development of new nanomaterials is gaining increasing attention due to their extensive applications in fields ranging from medicine to food and cultural heritage. Green nanoparticles provide advantages compared to conventional nanoparticles as their synthesis is environmentally-friendly and does not require the use of high temperatures, pressure, or toxic chemicals. In this paper, green silver nanoparticles (AgNPs) have been synthesized according to a new method using quercetin as a reducing agent at room temperature. The synthesized AgNPs were characterized using UV-Vis spectroscopy, transmission electron microscopy (TEM), energy dispersive spectroscopy (EDS), and dynamic light scattering (DLS) techniques and successively tested for biocide activity by studying their effects in the inhibition of bacterial growth. The results demonstrated that the smaller the AgNPs size, the greater their biocide activity. In particular, AgNPs with a diameter of 8 nm showed a minimum inhibitory concentration (MIC) value of 1.0 µg/mL against Streptococcus sp., Escherichia coli and Candida sp. microorganisms, while AgNPs with a larger diameter of about 20 nm were able to inhibit microbial of all selected pathogens at a higher MIC value of 2.5 µg/mL. © 2020 by the authors. Licensee MDPI, Basel, Switzerland.